An Analysis of Gender Stereotype in Television Commercial Advertisements in Indonesia - Usrul Khotimah, Siti; Umi Handayani, Maulisidiya; Kusumaningrum, Endah (International Proceedings of Nusantara Raya, 2022)
The media is one of the influential sources in shaping gender stereotypes among Indonesian people. The advertisements displayed in various television broadcasts tend to show a classification between masculine which is identical with men and feminine which is associated with women. The aims of this study are (1) to describe the gender stereotypes found in television advertisements in Indonesia; (2) Explaining the effect of gender stereotypes on advertising on product marketing. This research method uses a qualitative descriptive approach with the advertising object “Extra Joss, and Molto,". This study focuses on the selection of talents who play masculine and feminine characters in the advertisement. The data used in this study were obtained from various steps, including observing television advertisements as a form of population, selecting advertisements containing elements of gender stereotypes, and explaining the meaning of advertisements on television with contextual aspects. The results of the study show that advertising has a major impact on the preservation of gender stereotypes that have long existed in society. On the other hand, this also affects the consumer's interest in products according to the gender attached to their identity.